Quintuple Deglycosylation Mutant of Simian Immunodeficiency Virus SIVmac239 in Rhesus Macaques: Robust Primary Replication, Tightly Contained Chronic Infection, and Elicitation of Potent Immunity against the Parental Wild-Type Strain - Mori, Kazuyasu (American Society for Microbiology, 2001)
We previously generated a mutant of simian immunodeficiency virus (SIV) lacking 5 of a total of 22 N-glycans in its external envelope protein gp120 with no impairment in viral replication capability and infectivity in tissue culture cells. Here, we infected rhesus macaques with this mutant and found that it also replicated robustly in the acute phase but was tightly, though not completely, contained in the chronic phase. Thus, a critical requirement for the N-glycans for the full extent of chronic infection was demonstrated. No evidence indicating reversion to a wild type was obtained during the observation period of more than 40 weeks. Monkeys infected with the mutant were found to tolerate a challenge infection with wild-type SIV very well. Analyses of host responses following challenge revealed no neutralizing antibodies against the challenge virus but strong secondary responses of cytotoxic T lymphocytes against multiple antigens, including Gag-Pol, Nef, and Env. Thus, the quintuple deglycosylation mutant appeared to represent a novel class of SIV live attenuated vaccine.